To be or not to be of The Judiciary? Bibliographic approach on the process of reform, modernization, restructuring and refounding of the national judiciary - Domínguez Haro, Helder (2019)
This work identifies, from the bibliographic point of view, the different contributions, proposals, approaches and studies around the reform of the administration of justice in Peru, also called modernization, restructuring or refounding of the Judiciary. Notwithstanding the wide bibliography on this important subject, an interesting nucleus of publications corresponding to the 20th century and the beginning of the present century is reported. A first bibliographical review to promote research on the Peruvian judiciary and understand its historical evolution precedes a timely analysis of the author on the need for a change from the Judiciary itself, circumscribed to a democratic theory for judicial governance, and involves the participation of the different actors of the justice system and civil society, by a solid and predictable Judiciary as a support for constitutional democracy.